Portable equipment for projecting extinguishing agents supplied by firefighting pumps. Hand-held branchpipes for fire service use. Smooth bore jet and/or one fixed spray jet angle branchpipes PN 16 Part 3, (24th September 2019) - British Standards Institution,
No abstract available